Measuring progress toward empowerment: Women's empowerment in agriculture index: Baseline report - Malapit, Hazel J.; Sproule, Kathryn; Kovarik, Chiara; Meinzen-Dick, Ruth S.; Quisumbing, Agnes R.; Ramzan, Farzana; Hogue, Emily; Alkire, Sabina (International Food Policy Research Institute, 2014)
This report provides a comprehensive analysis of the Women’s Empowerment in Agriculture Index (WEAI) baseline survey results, summarizing both findings from the WEAI survey and the relationships between the WEAI and various outcomes of interest to the US Government’s Feed the Future initiative. These poverty, health, and nutrition outcomes include both factors that might affect empowerment and outcomes that might result from empowerment. The analysis includes thirteen countries from five regions and compares their baseline survey scores. WEAI scores range from a high of 0.98 in Cambodia to a low of 0.66 in Bangladesh.